Eksplorasi dan identifikasi Jamur Patogen Serangga di Rhizosfer Lahan Kering Kabupaten Malang - Agastya, I Made Indra; Ameliawati, Presti; Fikrinda, Wahyu (Jurnal Penelitian Pertanian Terapan, 2018)
This research was conducted by exploring insect pathogen in rhososphere of dry field of sugar cane of Malang Regency. The purpose of this research is to study the diversity of isolate insect pathogen in rhososphere of sugar cane plant in dry land of Malang Regency. Exploration activities of insect pathogens are carried out by isolating insect pathogens in dry land of sugarcane plant rhizosphere. Rizosphere soil sampling method using composite sampling technique is by taking diagonal soil samples at five points as deep as 5-10 cm, as much as 200 g at each sample point and isolation of insect pathogen type fungus using baiting method. The soil samples from the field were placed evenly over the petri dish. The soil above the petri dish is moistened and then the larvae of T miltor are placed for incubation for 48 hours. After 48 hours of dead larvae there will be a sign of an insect pathogenic fungus in the form of white hyphae on the surface of the T milter body. The marked larvae were then cultured on PDA media to be purified and identified morphologically, by looking at the color of hyphae. Observation miscroscopically using Burnet and Hunter determinations. Exploration and identification results found four specimens of fungi with Aspergilus sp species, Trichoderma sp, Beuveria sp, and Metharizium sp